Measuring patient safety: the Agency for Healthcare Research and Qualityís patient safety indicators (Italian Journal of Public Health, 2005)
There is a lot of interest in patient safety, but there is still little useable national level information on the actual magnitude of patient safety problems that can be used by providers and policy makers to judge performance.The AHRQ Patient Safety Indicators (PSIs) are a set of measures that can be used with hospital inpatient administrative (discharge) data to provide a perspective on patient safety. They screen for problems that patients experience as a result of exposure to the healthcare system and that are likely amenable to prevention by changes at the system or provider level. There is a growing interest in the possible use of the AHRQ PSIs in international settings.The Organization for Economic Cooperation and Development (OECD) maintains an ongoing project on Health Care Quality Indicators (HCQI) and whose goal is to develop a set of quality indicators that can be used to reliably assess quality of care across countries and raise questions about differences in quality of care internationally. Work is ongoing though a partnership between AHRQ and the Italian National Observatory on Health in the Italian Regions to test the AHRQ QIs with the Italian national hospital discharge data set. Preliminary results indicate that many of the operational issues associated with differences in coding schemes and data set structure are surmountable. With additional refinements on their clinical specificity, increased stability in their definitions over time to permit long-term monitoring and country interest within organizations such as the OECD to build on the existing scientific work of these indicators, their to help answer questions about patient safety worldwide will be significantly enhanced.
Keywords: patient safety; quality; indicators